Cerebral air embolism in pediatric patients undergoing cardiac surgery - Evyatar Hubara; Iris Motro Feingold; Yelena Skourikhin; Reut Kassif Lerner; Amir Vardi; David Mishaly; Uriel Katz; Omer Bar-Yosef (Journal of Cardiothoracic Surgery)
Abstract Objective Cerebral air embolism during Cardio-Pulmonary Bypass is a severe complication with significant neurological risks. We present six pediatric cases, detailing their presentation, management, and outcomes. The discussion reviews existing literature and proposes management guidelines for suspected air emboli. Methods A Case Series Report. A retrospective review of medical records was conducted to identify pediatric patients who experienced cerebral air embolism during cardiac surgeries with CPB between January 2009 to December 2023. Main findings Throughout the study duration, six patients experienced cerebral air emboli as a complication of their cardiac surgeries. Patients’ ages ranged from 8 months to 16 years, with five having single ventricle physiology. Tear-induced cerebral air emboli from right atrium dissection were observed in five cases. Seizures following surgery were the predominant clinical manifestation. Neurological outcomes varied; three patients showed minimal deficits at discharge, while other three cases suffered significant damage leading to substantial deficits. Conclusions We present a case series documenting the occurrence of a rare complication—cerebral air emboli—during cardiac surgery in children. Our study highlight a spectrum of neurological outcomes in affected patients and provides guidelines for the identification and treatment of this complication.